2017
DOI: 10.1515/amm-2017-0090
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Aspects of Bifocal Laser Welding of Trip Steels

Abstract: This work is concerned with comparative tests involving single-spot and twin-spot laser welding of thermomechanically rolled TRIP steel. The welding tests were carried out using keyhole welding and a solid state laser. In the case of twin-spot laser beam welding, the power distribution of beams was 50%:50%. The changes in macro-and microstructures were investigated using light and scanning electron microscopy. Three main zones subjected to the tests included the fusion zone, the heat affected zone and the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…As a result of high cooling rate they can precipitate in an uncontrolled way in a heat-affected zone and in the joint. Results of our previous study [25] performed on the 0.24C-1.55Mn-0.87Si-0.4Al-Nb-Ti type steel showed that it is weldable. The investigated steel was prepared by vacuum induction melting.…”
Section: Methodsmentioning
confidence: 87%
“…As a result of high cooling rate they can precipitate in an uncontrolled way in a heat-affected zone and in the joint. Results of our previous study [25] performed on the 0.24C-1.55Mn-0.87Si-0.4Al-Nb-Ti type steel showed that it is weldable. The investigated steel was prepared by vacuum induction melting.…”
Section: Methodsmentioning
confidence: 87%